Desarrollo e implementación de fórmula de silicona para mejorar la eficiencia en la producción de autoadhesivos en la planta de ARclad S.A. Cartagena empleando Six Sigma. (2023)
The Six Sigma methodology has been applied in quality and productivity improvement processes in various types of industries with excellent results, both in manufacturing and service companies. This paper presents the application of Six Sigma methodology tools to identify opportunities for improvement in the production of self-adhesive materials; with the aim of obtaining the development of a silicone formulation that increases the efficiency of the production plant. The importance of the Six Sigma methodology is highlighted as a very useful technique to reduce variability in the online lamination process of self-adhesive structures, allowing to minimize risks of release increases in the laminate.